Titanium silicalite molecular sieve material as well as preparation method and application thereof

By adjusting the ratio of silicon source, titanium source and template agent, and using multi-step hydrothermal treatment and peroxide treatment methods, titanium silicon molecular sieve with high content and multi-coordinated Ti species was prepared, solving the insufficient activity center of the existing titanium silicon molecular sieve. The problem of low titanium content of the skeleton significantly improves the catalytic performance.

CN119430215AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310955322.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The existing titanium silicon molecular sieve has insufficient active center in catalytic oxidation reaction and low titanium content in the skeleton, resulting in unsatisfactory catalytic effect.

Method used

By adjusting the ratio of silicon source, titanium source and template agent, and using multi-step hydrothermal treatment and peroxide treatment methods, titanium silicon molecular sieve with high content of multi-coordinated Ti species were prepared.

Benefits of technology

The catalytic performance of titanium silicon molecular sieve is significantly improved, and the catalytic activity, raw material conversion and product selectivity in cyclohexanone amoximetization reaction are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430215A_ABST
    Figure CN119430215A_ABST
Patent Text Reader

Abstract

The invention relates to a titanium silicalite molecular sieve material as well as a preparation method and application thereof. A titanium silicalite molecular sieve has the following UV-Vis characteristics: spectrum peaks respectively exist at 210 + / -10nm, 260 + / -10nm and 330 + / -10nm in a UV-Vis spectrum of the titanium silicalite molecular sieve; the peak area of a spectrum peak at the position of 210 + / -10 nm in the UV-Vis spectrum of the titanium silicalite molecular sieve is marked as I210, the peak area of a spectrum peak at the position of 260 + / -10 nm is marked as I260, the peak area of a spectrum peak at the position of 330 + / -10 nm is marked as I330, and I260gt; i210gt, I210gt; i330). The active center of the titanium silicalite molecular sieve can be effectively increased, the titanium content of the molecular sieve framework is improved, and good catalytic performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic material preparation, and in particular, to a titanium silicon molecular sieve material and a preparation method and application thereof. Background Art

[0002] Molecular sieves have high activity and product selectivity in many reactions due to their unique pore structure and active centers. Inserting titanium into the molecular sieve framework has opened up a new way to activate hydrogen peroxide and catalyze the conversion of organic matter under mild conditions. Among them, the discovery of TS-1 molecular sieve has laid the foundation for the development of new technologies for many oxidation reactions involving hydrogen peroxide, such as propylene epoxidation, cyclohexanone ammoximation, phenol hydroxylation, and thioether oxidation.

[0003] According to the distribution of different titanium atoms in TS-1, titanium species can be divided into tetracoordinate titanium species, penta- and hexacoordinate titanium species, anatase TiO2 and amorphous titanium species. Tetracoordinate framework titanium species have become the most studied and most widely recognized active species due to their good catalytic oxidation performance. A research paper (Chemical Engineering Journal 253 (2014) 464–471) pointed out that penta- and hexacoordinate titanium species in titanium silicate molecular sieves have strong catalytic oxidation performance like tetracoordinate framework titanium, while anatase TiO2 will cause H2O2 to self-decompose, which is not conducive to the catalytic oxidation reaction of TS-1. However, there is an upper limit value for the tetracoordinate titanium content of TS-1 (Si / Ti=39). Therefore, improving the catalytic oxidation activity of titanium silicate molecular sieves, increasing the content of tetracoordinate framework titanium and penta- and hexacoordinate titanium in TS-1, and avoiding the appearance of anatase species as much as possible will be the research focus.

[0004] Titanium silicate molecular sieve is a zeolite material with an MFI-type framework structure, and a quaternary ammonium-containing compound is usually used as an organic structure-directing agent during the synthesis process. Specifically, for example, US3702886 relates to ZSM-5 and a synthesis method thereof using tetrapropylammonium as a structure-directing agent in the synthesis. On the other hand, US4410501 relates to TS-1 zeolite and a method for synthesizing the same, and with respect to ZSM-5, it can be achieved with the aid of a tetrapropylammonium-containing compound.

[0005] However, the titanium silicate molecular sieve prepared by the existing process still has the problems of insufficient active centers and low skeleton titanium content, which makes it unable to obtain the ideal effect in the catalytic oxidation reaction. Summary of the invention

[0006] The purpose of the present disclosure is to provide a titanium silicon molecular sieve material and a preparation method and application thereof, which can effectively increase the active centers of the titanium silicon molecular sieve, improve the titanium content of the molecular sieve framework, and have good catalytic performance.

[0007] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a titanium silicate molecular sieve, wherein the titanium silicate molecular sieve has the following UV-Vis characteristics:

[0008] The titanium silicate molecular sieve has peaks at 210±10nm, 260±10nm and 330±10nm in the UV-Vis spectrum, respectively; the peak area of ​​the peak at 210±10nm in the UV-Vis spectrum of the titanium silicate molecular sieve is recorded as I 210 , the peak area of ​​the spectrum peak at 260±10nm is recorded as I 260 , the peak area of ​​the spectrum peak at 330±10nm is recorded as I 330 , where I 260 >I 210 >I 330 .

[0009] Optionally, X1 defined by the following formula (1) is any value in the range of 1.1 to 2.0:

[0010] X1=I 260 / I 210 Formula (1);

[0011] Optionally, X2 defined by the following formula (2) is any value in the range of 1.6 to 3.3:

[0012] X2=I 210 / I 330 Formula (2);

[0013] Optionally, X3 defined by the following formula (3) is any value in the range of 2.7 to 3.8:

[0014] X2=I 260 / I 330 Formula (3);

[0015] Preferably, X1 is any value in the range of 1.3 to 1.6, X2 is any value in the range of 2.0 to 2.8, and X3 is any value in the range of 2.9 to 3.5.

[0016] Optionally, the molar ratio of silicon to titanium in the titanium silicon molecular sieve is 1:10 to 100, preferably 1:16 to 34;

[0017] Preferably, the titanium silicate molecular sieve contains at least one cavity structure in the crystal; preferably, the size of a single cavity structure is 15nm to 40nm; further preferably, the total volume of the cavity structure accounts for 20% to 80% of the total volume of the titanium silicate molecular sieve, preferably 50% to 70%.

[0018] Optionally, the average particle size of the molecular sieve particles of the titanium silicon molecular sieve is 250nm to 400nm, preferably 310nm to 380nm; the BET specific surface area is 440m 2 / g~450m 2 / g, preferably 443m 2 / g~447m 2 / g; micropore volume is 0.16cm 3 / g~0.20cm 3 / g, preferably 0.17cm 3 / g~0.19cm 3 / g; mesopore volume is 0.08cm 3 / g~0.14cm 3 / g, preferably 0.10cm 3 / g~0.12cm 3 / g;

[0019] Optionally, the relative crystallinity of the titanium silicon molecular sieve is above 80%, preferably above 82%;

[0020] Preferably, there is a hysteresis loop between the adsorption isotherm and the desorption isotherm of low-temperature nitrogen adsorption of the titanium silicalite; preferably, the initial relative pressure (P / P0) at which the hysteresis loop appears is 0.4-0.5.

[0021] The second aspect of the present disclosure provides a method for preparing titanium silicon molecular sieve, comprising the following steps:

[0022] S1, mixing a silicon source, a titanium source, a first template and water, and performing a first hydrothermal treatment to obtain a molecular sieve intermediate product;

[0023] S2, mixing the molecular sieve intermediate product, the second template and water, and performing a second hydrothermal treatment;

[0024] Wherein, the first template is selected from one or more compounds having the structure shown in the following formula (M-1):

[0025] wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms;

[0026] The second template is selected from one or more compounds having the structure shown in the following formula (M-2):

[0027] Wherein R5, R6, R7 and R8 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms; and there is at least one alkenyl group among R5, R6, R7 and R8.

[0028] Optionally, in the formula (M-1) of the first template, R1, R2, R3 and R4 are each independently selected from one of an alkyl group having 3 carbon atoms and an alkenyl group having 3 carbon atoms;

[0029] In the formula (M-2) of the second template, R5, R6, R7 and R8 are each independently selected from one of an alkyl group having 3 carbon atoms and an alkenyl group having 3 carbon atoms;

[0030] Preferably, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide;

[0031] The second template is selected from one or more of allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably selected from allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; preferably selected from one or more of allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably selected from one or more of allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide.

[0032] Optionally, in step S1, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organic silicone grease, solid silica gel and white carbon black;

[0033] Optionally, the organic silicone grease is selected from one or more compounds having a structure represented by the following formula (A):

[0034]

[0035] R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate;

[0036] Optionally, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;

[0037] Preferably, the organic titanium source is a titanium-containing organic acid ester, selected from at least one of the structures represented by the following formula (B):

[0038]

[0039] Where R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;

[0040] Preferably, the inorganic titanium source is selected from one or more of chloride, nitrate or sulfate of titanium;

[0041] Further preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.

[0042] Optionally, in step S1, the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water is 1: (0.01-0.10): (0.05-0.30): (15-30), preferably 1: (0.03-0.06): (0.10-0.25): (18-25).

[0043] Optionally, in step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 150°C to 200°C, the hydrothermal time is 2h to 100h, and the hydrothermal crystallization pressure is the autogenous pressure; preferably, the hydrothermal temperature is 160°C to 190°C, and the hydrothermal crystallization time is 4h to 80h; further preferably, the hydrothermal temperature is 165°C to 188°C, and the hydrothermal crystallization time is 5h to 40h;

[0044] Optionally, before performing the first hydrothermal treatment, the method further comprises: performing a hydrolysis-dripping alcohol treatment on a raw material mixture obtained by mixing the silicon source, the titanium source, the first template and water; optionally, the conditions of the hydrolysis-dripping alcohol treatment include: treating at 5°C to 120°C for 0.5h to 48h; preferably treating at 50°C to 100°C for 1h to 24h.

[0045] Optionally, the method further comprises:

[0046] Drying and calcining the solid product obtained by the hydrothermal treatment in step S1 to obtain a first intermediate product;

[0047] Preferably, the method further comprises: contacting the first intermediate product with a peroxide for mixing treatment to obtain the molecular sieve intermediate product.

[0048] Optionally, the peroxide is selected from one or more of inorganic peroxides and organic peroxides; optionally, the inorganic peroxide is selected from one or more of hydrogen peroxide, potassium peroxide and sodium peroxide; the organic peroxide is selected from one or more of tert-butyl peroxide, cumene hydroperoxide and meta-chloroperbenzoic acid;

[0049] Optionally, the peroxide is used in the form of a solution, and the solvent of the peroxide solution is selected from one or more of water, alcohol compounds with 1 to 10 carbon atoms, ester compounds with 2 to 10 carbon atoms, and ketone compounds with 3 to 10 carbon atoms. Preferably, the solvent is selected from one or more of water, n-butanol, tert-butanol, ethanol, methanol, and cyclohexanol.

[0050] The peroxide concentration in the peroxide solution is 0.1 wt% to 10 wt%, preferably 0.3 wt% to 7 wt%; the pH value is 2.0 to 6.5, preferably 3.0 to 6.0, more preferably 3.7 to 5.0; the weight ratio of the peroxide solution to the first intermediate product is (0.5 to 50):1, preferably (1 to 40):1, more preferably (1.5 to 25):1.

[0051] Optionally, the conditions of the calcination treatment include: a calcination temperature of 350°C to 650°C, and a calcination time of 2h to 10h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 4h to 8h;

[0052] The conditions for mixing the second intermediate product with the peroxide include: a treatment temperature of 25°C to 100°C, preferably 50°C to 95°C, and more preferably 75°C to 85°C; a treatment time of 5min to 1440min, preferably 60min to 1200min, and more preferably 75min to 1000min; and a pressure of 0MPa to 5MPa, preferably 0.2MPa to 2.0MPa.

[0053] Optionally, in step S2, the weight ratio of the molecular sieve intermediate product: the second template: water is 1: (0.05-0.50): (1-10), preferably 1: (0.15-0.45): (2-6);

[0054] Optionally, the conditions of the second hydrothermal treatment include: temperature of 150°C to 200°C, time of 2h to 72h, and pressure of autogenous pressure; preferably, temperature of 160°C to 180°C, time of 12h to 48h

[0055] A third aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the second aspect of the present disclosure.

[0056] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the first aspect and the third aspect of the present disclosure in catalyzing organic reactions.

[0057] Optionally, the catalytic organic matter reaction includes propylene epoxidation to prepare propylene oxide, catalytic chlorohydrinization of allyl chloride to prepare dichloropropanol, and cyclohexanone oximation to prepare cyclohexanone oxime; optionally, the cyclohexanone oximation to prepare cyclohexanone oxime includes the following steps:

[0058] Under oximation reaction conditions, cyclohexanone, an oxidant, ammonia and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;

[0059] Optionally, the oxidant is selected from one or more of hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide and m-chloroperbenzoic acid; preferably, the reaction is carried out in the presence of a solvent; the solvent is selected from one or more of n-butanol, tert-butanol, ethanol, methanol and cyclohexanol;

[0060] Preferably, the oximation reaction conditions include: the molar ratio of the oxidant to cyclohexanone is 1.2 to 2.0:1, the molar ratio of the solvent to cyclohexanone is 0.5 to 5:1, the molar ratio of ammonia to cyclohexanone is 1.0 to 3.0:1, and the weight ratio of the catalyst to cyclohexanone is 0.05 to 0.2:1; the reaction temperature is 60 to 90°C, and the reaction time is 0.3 to 1.0h.

[0061] Through the above technical scheme, the present disclosure provides a titanium silicalite material, a preparation method and application thereof. The peak area of ​​the signal peak at the 260±10nm position in the UV-Vis spectrum of the titanium silicalite is higher than the signal peaks at other positions (210±10nm and 330±10nm). The titanium silicalite provided by the present disclosure contains a higher content of multi-coordinated Ti species. The titanium silicalite has a good effect in catalytic oxidation reactions. When used for preparing cyclohexanone oxime by ammoximation of cyclohexanone, it has high catalytic activity, high raw material conversion rate and high cyclohexanone oxime selectivity.

[0062] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0064] Figure 1 is the UV-Vis spectrum of the titanium silicate molecular sieve prepared in Example 1;

[0065] FIG2(a) is a nitrogen adsorption-desorption curve of the titanium silicon molecular sieve prepared in Example 1;

[0066] FIG2( b ) is a pore distribution diagram of the titanium silicon molecular sieve prepared in Example 1;

[0067] Figure 3 is a TEM image of the titanium silicon molecular sieve prepared in Example 1;

[0068] Figure 4 This is the XRD spectrum of the titanium silicon molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0069] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0070] The first aspect of the present disclosure provides a titanium silicate molecular sieve having the following UV-Vis characteristics:

[0071] The titanium silicate molecular sieve has peaks at 210±10nm, 260±10nm and 330±10nm in the UV-Vis spectrum, respectively; the peak area of ​​the peak at 210±10nm in the UV-Vis spectrum of the titanium silicate molecular sieve is recorded as I 210 , the peak area of ​​the spectrum peak at 260±10nm is recorded as I 260 , the peak area of ​​the spectrum peak at 330±10nm is recorded as I 330 , where I 260 >I 210 >I 330 .

[0072] The present disclosure provides a titanium silicalite molecular sieve. In the present disclosure, the peak at 210±10nm in the UV-Vis spectrum represents the framework tetracoordinated titanium species, the peak at 260±10nm represents the isolated hexacoordinated titanium species; the peak at 330±10nm represents anatase. The signal peak area at 260±10nm in the UV-Vis spectrum of the titanium silicalite molecular sieve is higher than that at other positions (210±10nm and 330±10nm), indicating that the titanium silicalite molecular sieve provided by the present disclosure contains a higher content of multi-coordinated Ti species. The titanium silicalite molecular sieve has a good effect in the catalytic oxidation reaction. When used for preparing cyclohexanone oxime by ammoximation of cyclohexanone, it has high catalytic activity, high raw material conversion rate and high cyclohexanone oxime selectivity.

[0073] The inventors of the present disclosure have found through experimental research that there is a certain proportional relationship between the peak area of ​​the peak at 260±10nm and the peak area of ​​the peak at 210±10nm in the UV-Vis spectrum of the titanium silicate molecular sieve, and the catalytic effect of the titanium silicate molecular sieve is better within this ratio range.

[0074] In one embodiment, X1 defined by the following formula (1) is any value in the range of 1.4 to 2.0:

[0075] X1=I 260 / I 210 Formula (1);

[0076] Optionally, X2 defined by the following formula (2) is any value in the range of 1.6 to 3.3:

[0077] X2=I210 / I 330 Formula (2);

[0078] Optionally, X3 defined by the following formula (3) is any value in the range of 2.7 to 3.8:

[0079] X2=I 260 / I 330 Formula (3).

[0080] In a preferred embodiment, X1 is any value in the range of 1.3 to 1.6, X2 is any value in the range of 2.0 to 2.8, and X3 is any value in the range of 2.9 to 3.5. When X1, X2 and X3 of the titanium silicate molecular sieve are within the range of this embodiment, the titanium silicate molecular sieve has a better catalytic effect in the catalytic oxidation reaction.

[0081] In a specific embodiment, the molar ratio of silicon element to titanium element is 1:10-100, preferably 1:16-34.

[0082] In a preferred embodiment, the titanium silicon molecular sieve crystal contains at least one cavity structure; preferably, the size of a single cavity structure is 15nm to 40nm. The titanium silicon molecular sieve crystal provided in the present disclosure has one or more cavity structures, which is beneficial to improving the diffusion performance of the molecular sieve, accelerating the reaction rate, and extending the life of the catalyst. The cavity structure and its size in the present disclosure are obtained by transmission electron microscopy testing. In the present disclosure, the size of the cavity structure refers to the length between two positions on the cavity wall passing through the center of the cavity structure in the transmission electron microscopy photograph of the molecular sieve; for example, "the size of a single cavity structure is 15nm to 40nm" means that the length between two positions on the cavity wall passing through the center of the cavity structure in any cavity structure in the molecular sieve is within the range of 15nm to 40nm.

[0083] In one embodiment, the total volume of the cavity structure accounts for 30% to 80% of the total volume of the titanium silicalite molecular sieve, preferably 50% to 70%.

[0084] In a specific embodiment, the titanium silicon molecular sieve comprises molecular sieve particles composed of a plurality of crystal grains with approximately right-angled edges, and the molecular sieve particles have a right-angled edge morphology; the right-angled edge angle ranges from 90°±10°.

[0085] In one embodiment, the average particle size of the molecular sieve particles of the titanium silicon molecular sieve is 250nm to 400nm, preferably 310nm to 380nm; the BET specific surface area is 440m 2 / g~450m 2 / g, preferably 443m 2 / g~447m 2 / g; micropore volume is 0.16cm 3 / g~0.20cm 3 / g, preferably 0.17cm 3 / g~0.19cm 3 / g; mesopore volume is 0.08cm 3 / g~0.14cm 3 / g, preferably 0.10cm 3 / g~0.12cm 3 / g.

[0086] In a preferred embodiment, a hysteresis loop exists between the adsorption isotherm and the desorption isotherm of low-temperature nitrogen adsorption of the titanium silicalite; preferably, the starting relative pressure (P / P0) at which the hysteresis loop appears is 0.4 to 0.5, preferably 0.42 to 0.48.

[0087] In a specific embodiment, the relative crystallinity of the titanium silicon molecular sieve is 80% or more, preferably 82% or more. For example, the MFI structure is characterized by XRD, and the MFI-type all-silicon molecular sieve S-1 is used as a reference sample, and its relative crystallinity is greater than 80%, preferably greater than 82%. The titanium silicon molecular sieve provided by the present disclosure has a high relative crystallinity.

[0088] In a specific embodiment, the titanium silicalite molecular sieve can have AEL, AFI, AFN, BEC, CFI, CHA, CON, EUO, FAU, FER, IMF, LTA, MER, MFI, MEL, MOR, MWW, RHO, TON, *BEA, *EWT, or a two-dimensional hexagonal phase structure, among which the MFI structure is preferred.

[0089] In a specific embodiment, the titanium silicon molecular sieve provided by the present disclosure can be used as a catalytic active component, and its unique skeleton elements can be used, or it can be used as a carrier to further load active centers, or it can be prepared into a catalyst by mechanical mixing, kneading, tableting, extrusion, spraying, rolling ball, oil column, etc. with other catalysts, co-catalysts, structural additives, electronic additives, binders, inert carriers, etc. The reagents and preparation processes used can all be conventional reagents or processes in the art.

[0090] A second aspect of the present disclosure provides a method for preparing a titanium silicon molecular sieve, comprising the following steps:

[0091] S1, mixing a silicon source, a titanium source, a first template and water, and performing a first hydrothermal treatment to obtain a molecular sieve intermediate product;

[0092] S2, mixing the molecular sieve intermediate product, the second template and water, and performing a second hydrothermal treatment;

[0093] Wherein, the first template is selected from one or more compounds having the structure shown in the following formula (M-1):

[0094] wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms;

[0095] The second template is selected from one or more compounds having the structure shown in the following formula (M-2):

[0096] Wherein R5, R6, R7 and R8 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms; and there is at least one alkenyl group among R5, R6, R7 and R8.

[0097] The present disclosure provides a method for preparing titanium silicalite molecular sieves, using organic ammonium hydroxide compounds represented by the above formulas (M-1) and (M-2) as the first template and the second template, and the first template and the second template contain alkenyl groups, especially the second template contains at least one alkenyl group, which can interact with titanium species and promote the insertion of titanium into the framework, so as to prepare a molecular sieve with a high content of isolated hexacoordinated titanium species.

[0098] In one embodiment, in the formula (M-1) of the first template, R1, R2, R3 and R4 are each independently selected from one of an alkyl group having 3 carbon atoms and an alkenyl group having 3 carbon atoms;

[0099] In the formula (M-2) of the second template, R5, R6, R7 and R8 are each independently selected from one of an alkyl group having 3 carbon atoms and an alkenyl group having 3 carbon atoms.

[0100] In a specific embodiment, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide;

[0101] The second template is selected from one or more of allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably selected from allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; preferably selected from one or more of allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably selected from one or more of allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide.

[0102] In one embodiment, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organic silicone grease, solid silica gel and white carbon black. Preferably, the SiO2 content in the solid silicon source (solid silica gel, white carbon black and silica sol) is not less than 99.99% by weight based on dry weight, and the total mass content of Fe, Al and Na impurities is less than 10ppm; for example, the SiO2 content is 99.99-100% by weight, usually greater than 99.99 and less than 100% by weight. The solid silicon source can be high-purity silica gel and / or white carbon black, preferably white carbon black; wherein the SiO2 content in the high-purity silica gel is preferably greater than or equal to 99.99% by weight, for example, greater than 99.99% by weight and less than 100% by weight, and the total mass content of Fe, Al and Na impurities is less than 10ppm. Based on the dry weight of the white carbon black, the SiO2 content in the white carbon black is preferably greater than or equal to 99.99 weight %, for example, 99.99 to 100 weight %, for example, greater than 99.99 weight % and less than 100 weight %, and the total mass content of Fe, Al and Na impurities in the white carbon black is less than 10 ppm in terms of atoms. The specific surface area of ​​the white carbon black is between 20 and 1000 m 2 / g, preferably 50 to 400 m 2 / g.

[0103] In a preferred embodiment, the organic silicone grease is selected from one or more compounds having the structure shown in the following formula (A):

[0104]

[0105] R a , R b , R c and R dEach is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate.

[0106] In one embodiment, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;

[0107] Preferably, the organic titanium source is a titanium-containing organic acid ester, selected from at least one of the structures represented by the following formula (B):

[0108]

[0109] Where R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;

[0110] Preferably, the inorganic titanium source is selected from one or more of chloride, nitrate or sulfate of titanium;

[0111] Further preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.

[0112] In the present disclosure, the silicon source, the titanium source, the first template, the second template and the third template can be purchased through common commercial channels, or prepared by known methods.

[0113] In one embodiment, in step S1, the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water is 1: (0.01-0.10): (0.05-0.30): (15-30), preferably 1: (0.03-0.06): (0.10-0.25): (18-25). The titanium silicon molecular sieve is prepared according to the optimized raw material molar ratio in this embodiment, which can further improve the catalytic performance of the titanium silicon molecular sieve.

[0114] In one embodiment, in step S1, the conditions of the first hydrothermal treatment include: a hydrothermal temperature of 150°C to 200°C, a hydrothermal time of 2h to 100h, and a hydrothermal crystallization pressure of autogenous pressure; preferably, the hydrothermal temperature is 160°C to 190°C, and the hydrothermal crystallization time is 4h to 80h; further preferably, the hydrothermal temperature is 165°C to 188°C, and the hydrothermal crystallization time is 5h to 40h. The catalytic performance of the molecular sieve can be further improved according to the optimized hydrothermal crystallization treatment conditions in this embodiment.

[0115] In a specific embodiment, before performing the first hydrothermal treatment, the method further includes: performing a hydrolysis-dripping alcohol treatment on the raw material mixture obtained by mixing the silicon source, the titanium source, the first template and water; optionally, the conditions of the hydrolysis-dripping alcohol treatment include: treating at 5°C to 120°C for 0.5h to 48h; preferably treating at 50°C to 100°C for 1h to 24h.

[0116] In a preferred embodiment, the method further comprises:

[0117] The solid product obtained by the hydrothermal treatment in step S1 is dried and calcined to obtain a first intermediate product; the first intermediate product is contacted with a peroxide for mixing to obtain the molecular sieve intermediate product. In the present disclosure, the drying treatment can remove most of the water in the molecular sieve to reduce the amount of water evaporation during calcination, and the temperature of the drying treatment can be 100-200°C; the calcination treatment can remove the template in the molecular sieve to obtain a titanium silicon molecular sieve without a template; the present disclosure uses peroxide to treat the titanium silicon molecular sieve intermediate product, which can be beneficial to the formation of a multi-level pore structure of the titanium silicon molecular sieve and improve the performance of the molecular sieve; and compared with the traditional hydrochloric acid treatment, the use of peroxide to treat the titanium silicon molecular sieve avoids the acid corrosion of the device and the chlorine corrosion of the catalyst caused by hydrochloric acid in industrial applications, and the hydrochloric acid treatment of the molecular sieve requires the introduction of ammonia water for neutralization, which produces a large amount of nitrogen-containing wastewater. The present disclosure uses peroxide treatment to effectively avoid the generation of nitrogen-containing wastewater.

[0118] In a specific embodiment, the peroxide is selected from one or more of inorganic peroxides and organic peroxides; optionally, the inorganic peroxide is selected from one or more of hydrogen peroxide, potassium peroxide and sodium peroxide; the organic peroxide is selected from one or more of tert-butyl peroxide, cumene hydroperoxide and meta-chloroperbenzoic acid;

[0119] Optionally, the peroxide is used in the form of a solution, and the solvent of the peroxide solution is selected from one or more of water, alcohol compounds with 1 to 10 carbon atoms, ester compounds with 2 to 10 carbon atoms, and ketone compounds with 3 to 10 carbon atoms. Preferably, the solvent is selected from one or more of water, n-butanol, tert-butanol, ethanol, methanol, and cyclohexanol.

[0120] The peroxide concentration in the peroxide solution is 0.1 wt% to 10 wt%, preferably 0.3 wt% to 7 wt%; the pH value is 2.0 to 6.5, preferably 3.0 to 6.0, more preferably 3.7 to 5.0; the weight ratio of the peroxide solution to the first intermediate product is (0.5 to 50):1, preferably (1 to 40):1, more preferably (1.5 to 25):1.

[0121] In a preferred embodiment, the conditions of the calcination treatment include: a calcination temperature of 350°C to 650°C and a calcination time of 2h to 10h; preferably, a calcination temperature of 450°C to 600°C and a calcination time of 4h to 8h;

[0122] The conditions for mixing the second intermediate product with the peroxide include: a treatment temperature of 25°C to 100°C, preferably 50°C to 95°C, and more preferably 75°C to 85°C; a treatment time of 5min to 1440min, preferably 60min to 1200min, and more preferably 75min to 1000min; and a pressure (gauge pressure) of 0MPa to 5MPa, preferably 0.2MPa to 2MPa.

[0123] In the present disclosure, before the solid product obtained by the hydrothermal treatment in step S1 is dried, the product obtained by the hydrothermal treatment is filtered and washed. The filtering is to separate the titanium silicon molecular sieve obtained by crystallization from the crystallization mother liquor. The purpose of washing is to wash away the template adsorbed on the surface of the molecular sieve particles. For example, the mixed washing or elution can be performed at a temperature of room temperature to 50°C and a weight ratio of the molecular sieve to water of 1:1 to 20, for example, at a mixing ratio of 1:(1 to 15).

[0124] In one embodiment, in step S2, the weight ratio of the molecular sieve intermediate product: the second template: water is 1: (0.05-0.50): (1-10), preferably 1: (0.15-0.45): (2-6).

[0125] In one embodiment, the conditions of the second hydrothermal treatment include: temperature of 150°C to 200°C, time of 2h to 72h, and pressure of autogenous pressure; preferably, temperature of 160°C to 180°C, time of 12h to 48h.

[0126] A third aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the second aspect of the present disclosure.

[0127] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the first aspect and the third aspect of the present disclosure in the catalytic reaction of organic matter and / or the adsorption separation process.

[0128] In the present disclosure, the organic matter reaction includes: catalytic oxidation reaction (olefin oxidation / epoxidation to prepare aldehydes, ketones, acids, epoxy compounds, vicinal diols; alkane oxidation to prepare alcohols, aldehydes, acids; alcohol oxidation to prepare ketones, acids; aldehyde oxidation to prepare acids; aromatic oxidation to prepare phenols; sulfide oxidation to prepare sulfoxides and sulfones), reduction reaction, oximation reaction (aldehyde / ketone ammoximation to prepare amides and lactams), aldol condensation reaction, substitution / halogenation reaction, elimination reaction, transesterification reaction, dehydration reaction, etherification reaction, esterification reaction, double bond / triple bond addition reaction, diene addition reaction, Beckmann rearrangement reaction (cyclohexanone oxime gas phase rearrangement to prepare caprolactam), hydrogen transfer reaction, etc. The adsorption separation process includes: adsorption separation of hydrocarbons (such as ethane ethylene, butene dibutylene), gas (such as helium separation), inorganic matter (such as cesium ion separation) and other substances.

[0129] In a specific embodiment, the organic matter catalytic reaction includes oximation of cyclohexanone to prepare cyclohexanone oxime; optionally, the reaction includes the following steps:

[0130] Under oximation reaction conditions, cyclohexanone, an oxidant, ammonia and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;

[0131] Optionally, the oxidant is selected from one or more of hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide and m-chloroperbenzoic acid; preferably, the reaction is carried out in the presence of a solvent; the solvent is selected from one or more of n-butanol, tert-butanol, ethanol, methanol and cyclohexanol;

[0132] Preferably, the oximation reaction conditions include: the molar ratio of the oxidant to cyclohexanone is 1.2 to 2.0:1, the molar ratio of the solvent to cyclohexanone is 0.5 to 5:1, the molar ratio of ammonia to cyclohexanone is 1.0 to 3.0:1, and the weight ratio of the catalyst to cyclohexanone is 0.05 to 0.2:1; the reaction temperature is 60 to 90°C, and the reaction time is 0.3 to 1.0h.

[0133] In the application of the titanium silicalite provided in the present disclosure, the titanium silicalite or the catalyst containing the titanium silicalite can be used in the form of powder or shaped spheres, strips, cakes, granules, etc., and can be mixed with other catalysts; the application can be carried out in various reactors such as kettle reactors, slurry bed reactors, fixed bed reactors, fluidized bed reactors, moving bed reactors, microchannel reactors, etc.; the reaction raw materials and catalysts can be fed all at once, intermittently, or continuously.

[0134] It will be understood by those skilled in the art that the separation of the product and the catalyst can be achieved in a variety of ways. For example, when the original powdered molecular sieve is used as the catalyst, the product separation and the catalyst recovery and reuse can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation, etc. Alternatively, the catalyst can be formed and loaded into a fixed bed reactor, and the catalyst can be recovered after the reaction is completed. The separation and recovery methods of various catalysts can be known methods.

[0135] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.

[0136] In the following embodiments and comparative examples:

[0137] The structure of the molecular sieve was determined by XRD analysis, and the test instrument was Siemens D5005 X-ray diffractometer; the test method included: Cu target, Kα radiation, Ni filter, tube point voltage 40kV, tube current 250mA, scintillation counter, step width 0.02°. Scanning range 2θ = 5° to 35°, scanning rate 0.4 (°) / min.

[0138] The chemical composition of the molecular sieves was determined by XRF analysis.

[0139] The specific surface area of ​​the molecular sieve is measured by nitrogen low-temperature adsorption desorption method, and the micropore specific surface area is calculated by BET method; the pore volume and pore distribution are determined according to the method described in RIPP151-90 in "Petrochemical Analysis Methods" compiled by Yang Cuiding et al. (Science Press, first edition, published in September 1990).

[0140] The high-resolution morphology analysis of molecular sieves was characterized by TEM method. The test instrument was FEI's TECNAIG2F20 (200kV) transmission electron microscope. The test method included preparing samples by suspension method, taking 0.01g of HTS molecular sieve sample and putting it into a 2ml sample bottle; adding anhydrous ethanol to disperse, shaking evenly, taking a drop on a 3mm sample net, drying it, putting it into the injector, and inserting it into the electron microscope for observation. The acceleration voltage was 20kV.

[0141] The testing instrument for the UV-visible spectrum analysis is a JASCO UV-visible 550 UV spectrophotometer. The testing method includes tablet pressing and a scanning range of 190 to 800 nm.

[0142] Unless otherwise specified, the raw materials used in the examples and comparative examples were all analytically pure reagents.

[0143] Example 1

[0144] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:20, allyl tripropylammonium hydroxide (first template, ATPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 68°C for about 20 hours to obtain a sol, and then crystallized at 170°C for 24 hours (first hydrothermal treatment); thereafter, the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a first intermediate product, which is then mixed with a hydrogen peroxide solution (the solvent is tert-butyl alcohol, the hydrogen peroxide concentration is 1 weight%, and the pH value is 5.0), the weight ratio of the peroxide solution to the first intermediate product is 5:1, the mixing treatment temperature is 80°C, the treatment time is 200 min; the pressure is 0.7MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.22:3, and hydrothermally treated at 180°C for 38h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-A.

[0145] The UV-Vis spectrum and peak separation results of titanium silicalite TS-1-A are as follows: Figure 1 As shown, it can be seen that the titanium silicalite has peaks at 210±10nm, 260±10nm and 330±10nm in the UV-Vis spectrum, wherein the peak area I of the peak at 210±10nm is 210 is 33.9 (because the UV spectrum scan starts at 190nm, Figure 1 The peak area of ​​the spectrum peak at 210±10nm is calculated by integration from 190nm), and the peak area of ​​the spectrum peak at 260±10nm is calculated by integration from 190nm. 260 The peak area I of the spectrum peak at the position of 330±10nm is 50.8. 330 is 15.4, I 260 >I 210 >I 330 ; X1 calculated by formula (1) is 1.5, X2 calculated by formula (2) is 2.2, and X3 calculated by formula (3) is 3.3;

[0146] The nitrogen adsorption and desorption curve of titanium silicalite TS-1-A is shown in Figure 2(a), and the pore distribution diagram is shown in Figure 2(b). It can be seen from Figure 2(a) that there is a hysteresis loop between the adsorption isotherm and desorption isotherm of low-temperature nitrogen adsorption of titanium silicalite; the starting relative pressure (P / P0) of the hysteresis loop is 0.45. It can be seen from Figure 2(b) that there are abundant mesopores inside the molecular sieve;

[0147] TEM image of titanium silicate molecular sieve TS-1-A Figure 3 As shown by Figure 3 It can be seen that the particle size of the molecular sieve particles is 360nm, and the molecular sieve grains have a right-angled morphology formed by the aggregation and growth of multiple small grains with approximately right-angled edges. There are multiple cavity structures in the molecular sieve crystals, and the size of a single cavity structure is about 20-25nm; the total volume of the cavity structure accounts for 55% of the total volume of the titanium silicon molecular sieve;

[0148] The XRD spectrum of titanium silicate molecular sieve TS-1-A is as follows Figure 4 As shown by Figure 4 It can be seen that the molecular sieve has an MFI structure ( Figure 4 Diffraction peaks shown in dashed boxes).

[0149] Example 2

[0150] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:30, allyl tripropylammonium hydroxide (first template, ATPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 75°C for about 17 hours to obtain a sol, and then crystallized at 186°C for 37 hours (first hydrothermal treatment). After that, the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a first intermediate product, which is then mixed with a hydrogen peroxide solution (the solvent is tert-butyl alcohol, the hydrogen peroxide concentration is 5 weight%, and the pH value is 4), the weight ratio of the peroxide solution to the first intermediate product is 3:1, the mixing treatment temperature is 55°C, the treatment time is 800min; the pressure is 0.5MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.43:6, and hydrothermally treated at 169°C for 24h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-B.

[0151] Example 3

[0152] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.03:0.15:20, allyl tripropyl ammonium hydroxide (first template, ATPAOH, 25 weight %) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 85°C for about 15 hours to obtain a sol; then crystallization is carried out at 168°C for 25 hours (first hydrothermal treatment), and then the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a first intermediate product; then mixed with tert-butyl hydroperoxide solution (solvent is tert-butyl alcohol, peroxide concentration is 6 weight %, pH value is 4.3), the weight ratio of the peroxide solution to the first intermediate product is 10:1, the mixing treatment temperature is 83°C, the treatment time is 1000min; the pressure is 1MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with the weight ratio of molecular sieve intermediate: second template: water being 1:0.15:2, and hydrothermally treated at 166°C for 47h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-C.

[0153] Example 4

[0154] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.15:20, tetrapropylammonium hydroxide (first template, TPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 76°C for about 19 hours to obtain a sol, and then crystallized at 167°C for 35 hours (first hydrothermal treatment); thereafter, the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a first intermediate product, which is then mixed with a hydrogen peroxide solution (the solvent is tert-butyl alcohol, the hydrogen peroxide concentration is 0.5 weight%, and the pH value is 4.0), the weight ratio of the peroxide solution to the first intermediate product is 15:1, the mixing treatment temperature is 75°C, the treatment time is 900 min; the pressure is 0.9 MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.35:2.5, and hydrothermally treated at 178°C for 23h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-D.

[0155] Example 5

[0156] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:20, tetrapropylammonium hydroxide (first template, TPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 65°C for about 20 hours to obtain a sol, and then crystallized at 178°C for 40 hours (first hydrothermal treatment), and then the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a first intermediate product, which is then mixed with tert-butyl hydroperoxide solution (solvent is tert-butyl alcohol, peroxide concentration is 7 weight%, pH value is 3.7), the weight ratio of the peroxide solution to the first intermediate product is 25:1, the mixing treatment temperature is 85°C, the treatment time is 75min; the pressure is 1.5MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.40:5, and hydrothermally treated at 168°C for 33h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-E.

[0157] Example 6

[0158] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:20, tetrapropylammonium hydroxide (first template, TPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 72°C for about 14 hours to obtain a sol; then crystallization is carried out at 169°C for 38 hours (first hydrothermal treatment); thereafter, the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a first intermediate product; then mixed with a hydrogen peroxide solution (the solvent is tert-butyl alcohol, the peroxide concentration is 4 weight%, and the pH value is 4.2), the weight ratio of the peroxide solution to the first intermediate product is 1.5:1, the mixing treatment temperature is 78°C, the treatment time is 400min; the pressure is 0.2MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate product was then mixed with propylene tripropylammonium hydroxide (the second template, 20 wt%) and water, with the weight ratio of the molecular sieve intermediate product: the second template: water being 1:0.45:4, and hydrothermally treated at 167°C for 25h (the second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-F.

[0159] Example 7

[0160] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:30, allyl tripropyl ammonium hydroxide (first template, ATPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water were stirred at 79°C for about 8 hours to obtain a sol, and then crystallized at 170°C for 30 hours (first hydrothermal treatment), and then the solid obtained by centrifugation was filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve intermediate. It was then mixed with ATPAOH (second template, 25 wt%) and water, the weight ratio of molecular sieve intermediate: second template: water was 1:0.2:2.5, and hydrothermally treated at 172°C for 18 hours (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-G.

[0161] Example 8

[0162] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.03:0.20:30, allyltripropylammonium hydroxide (first template, ATPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 75°C for about 6 hours to obtain a sol, which is then crystallized at 182°C for 20 hours (first hydrothermal treatment). The solid obtained by centrifugation is then filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve intermediate. It was then mixed with allyltripropylammonium hydroxide (the second template, 16 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.4:4, and hydrothermally treated at 167°C for 32h (the second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-H.

[0163] Example 9

[0164] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.03:0.15:30, allyl tripropyl ammonium hydroxide (first template, ATPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water were stirred at 63°C for about 18 hours to obtain a sol; then crystallized at 165°C for 10 hours (first hydrothermal treatment), and then the solid obtained by centrifugation was filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve intermediate product. Then it was mixed with ATPAOH (second template, 25 wt%) and water, the weight ratio of molecular sieve intermediate product: second template: water was 1:0.45:6, and hydrothermally treated at 173°C for 16 hours (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-I.

[0165] Example 10

[0166] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:20, tetrapropylammonium hydroxide (TPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water were stirred at 79°C for about 10 hours to obtain a sol, and then crystallized at 175°C for 6 hours (first hydrothermal treatment), and then the solid obtained by centrifugation was filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve intermediate. It was then mixed with ATPAOH (second template, 25 wt%) and water, the weight ratio of molecular sieve intermediate: second template: water was 1:0.15:3.2, and hydrothermally treated at 184°C for 27 hours (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-J.

[0167] Embodiment 11

[0168] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.03:0.15:30, allyl tripropyl ammonium hydroxide (ATPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water were stirred at 69°C for about 17 hours to obtain a sol, and then crystallized at 153°C for 8 hours (first hydrothermal treatment), and then the solid obtained by centrifugation was filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve intermediate. It was then mixed with diallyl dipropyl ammonium hydroxide (second template, 30 wt%) and water, the weight ratio of molecular sieve intermediate: second template: water was 1:0.33:5, and hydrothermally treated at 188°C for 25 hours (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-K.

[0169] Example 12

[0170] This example refers to the preparation method of Example 1, and the difference from Example 1 is that the silicon source tetraethyl orthosilicate (TEOS) is replaced by white carbon black, the titanium source n-butyl titanate [TBOT] is replaced by titanium tetrachloride, and the first template is replaced by diallyldipropylammonium hydroxide. The rest of the process is the same as that of Example 1, and a molecular sieve solid is obtained, which is numbered TS-1-L.

[0171] Embodiment 13

[0172] This embodiment refers to the preparation method of Example 1, and the difference from Example 1 is that: allyl tripropylammonium hydroxide solution, tetraethyl orthosilicate, n-butyl titanate and deionized water are added in a molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.1:0.05:30; the weight ratio of molecular sieve intermediate product: second template: water is 1:0.1:10; the rest of the process is the same as in Example 1, and a molecular sieve solid is obtained, which is numbered TS-1-M.

[0173] Embodiment 14

[0174] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:20, allyl tripropylammonium hydroxide (first template, ATPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 68°C for about 20 hours to obtain a sol, and then crystallized at 150°C for 2 hours (first hydrothermal treatment); then the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 350°C for 10 hours to obtain a first intermediate product, which is then mixed with a hydrogen peroxide solution (the solvent is tert-butyl alcohol, the hydrogen peroxide concentration is 1 weight%, and the pH value is 6.5), the weight ratio of the peroxide solution to the first intermediate product is 50:1, the mixing treatment temperature is 100°C, the treatment time is 50 minutes; the pressure is 0.7MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.22:3, and hydrothermally treated at 150°C for 8h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-N.

[0175] Embodiment 15

[0176] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.5:1:100, allyl tripropylammonium hydroxide (first template, ATPAOH, 25 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 68°C for about 20 hours to obtain a sol, and then crystallized at 250°C for 0.5h (first hydrothermal treatment); then the solid obtained by centrifugation is filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 300°C for 10h to obtain a first intermediate product, which is then mixed with a hydrogen peroxide solution (the solvent is tert-butyl alcohol, the hydrogen peroxide concentration is 1 weight%, and the pH value is 6.5), the weight ratio of the peroxide solution to the first intermediate product is 80:1, the mixing treatment temperature is 120°C, the treatment time is 50min; the pressure is 0.7MPa, and a molecular sieve intermediate product is obtained. The molecular sieve intermediate was then mixed with ATPAOH (second template, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:1:20, and hydrothermally treated at 300°C for 1 h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered TS-1-O.

[0177] Comparative Example 1

[0178] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.15:20, tetrapropylammonium hydroxide (first template, TPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water were stirred at 68°C for about 22 hours to obtain a sol, which was then crystallized at 182°C for 30 hours. The solid obtained by centrifugation was then filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours. h, to obtain a first intermediate, which is then mixed with a hydrochloric acid solution (hydrochloric acid, concentration 2 weight %), the conditions for the hydrochloric acid treatment include: a weight ratio of the first intermediate to hydrochloric acid of 1:15, a treatment temperature of 75°C, a treatment time of 3h, and an appropriate amount of ammonia water is added after the hydrochloric acid treatment to neutralize the molecular sieve intermediate to obtain the molecular sieve intermediate, which is filtered and dried and mixed with TPAOH (a second template, 25 weight %) and water, the weight ratio of the molecular sieve intermediate: the second template: water is 1:0.3:3, and is hydrothermally treated at 163°C for 30h to obtain a molecular sieve solid, numbered D-1.

[0179] Comparative Example 2

[0180] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.15:20, tetrapropylammonium hydroxide (TPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water were stirred at 87°C for about 7 hours to obtain a sol, which was then crystallized at 163°C for 25 hours, and then the solid obtained by centrifugation was filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours. It was then mixed with TPAOH and water and hydrothermally treated at 185°C for 13 hours to obtain a molecular sieve solid, numbered D-2.

[0181] Comparative Example 3

[0182] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.15:20, tetrapropylammonium hydroxide (TPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 65°C for about 12 hours to obtain a sol, to which N-phenyl-aminopropyl-trimethoxysilane is added, with a molar ratio of N-phenyl-aminopropyl-trimethoxysilane to SiO2 of 0.04, and then crystallized at 175°C for 26 hours. The solid obtained by centrifugation is then filtered, washed with deionized water, dried at 100°C for 3 hours, calcined at 550°C for 6 hours, and then mixed with a hydrochloric acid solution. The acid treatment conditions are the same as those in Comparative Example 1. After the hydrochloric acid treatment, an appropriate amount of ammonia water is added for neutralization. It was then mixed with TPAOH and water and hydrothermally treated at 173°C for 17 h to obtain a molecular sieve solid, numbered D-3.

[0183] Comparative Example 4

[0184] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.20:20, allyltripropylammonium hydroxide (first template, ATPAOH, 25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [TBOT] and deionized water are stirred at 78°C for about 6 hours to obtain a sol, which is then crystallized at 188°C for 12 hours (first hydrothermal treatment). The solid obtained by centrifugation is then filtered, washed with deionized water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve intermediate. It was then mixed with tetrapropylammonium hydroxide (the second template, TPAOH, free of olefin groups, 25 wt%) and water, with a weight ratio of molecular sieve intermediate: second template: water of 1:0.35:5, and hydrothermally treated at 165°C for 50 h (second hydrothermal treatment) to obtain a molecular sieve solid, numbered D-4.

[0185] The UV-Vis spectrum characteristics, molecular sieve configuration, titanium-silicon molar ratio, and relative crystallinity of the molecular sieve products obtained in the above examples and comparative examples are listed in Table 1 below; the structural parameters and other data of the molecular sieve products obtained in the above examples and comparative examples are listed in Table 2 below.

[0186] Table 1

[0187]

[0188]

[0189] Table 2

[0190]

[0191] Application test case

[0192] This test example is used to evaluate the performance of the titanium silicon molecular sieve prepared in the comparative example and the example as a catalyst in catalyzing the ammoximation reaction of cyclohexanone. Specifically, it includes the following process:

[0193] The ammoximation reaction of cyclohexanone was carried out in a 250ml three-necked flask reaction device with an automatic temperature-controlled water bath, magnetic stirring and condensation reflux system. The samples prepared in the above embodiments and comparative examples were added into a three-necked flask (the mass ratio of catalyst to cyclohexanone was 0.1) according to the sample amount of 1.00g, 10g (0.14mol) of solvent tert-butyl alcohol, and 9.8g (0.1mol) of cyclohexanone, respectively, and placed in a water bath with a preset reaction temperature of 80°C. A peristaltic pump was used to dropwise add 13.7g (0.12mol) of hydrogen peroxide with a mass fraction of 30% by weight and 28.1g (0.2mol) of ammonia water with a mass fraction of 25% by weight, respectively, wherein the molar ratio of cyclohexanone: ammonia water: hydrogen peroxide: solvent was 1:2:1.2:1.35. The reaction was stopped after 0.5h, the temperature was rapidly lowered, and the liquid product was separated by suction filtration, and the composition was determined. The results are listed in Table 3 below.

[0194] For the long-cycle reaction, 1.00 g of the obtained sample was placed in a 100 mL slurry bed reactor with continuous feeding and membrane separation device, and hydrogen peroxide with a mass fraction of 30% by weight was added at 24.7 mL / h, ammonia with a mass fraction of 25% by weight was added at 61.7 mL / h, and a mixture of cyclohexanone and tert-butanol (cyclohexanone and tert-butanol volume ratio of 1:2) was added at 72.2 mL / h under stirring, and the material was continuously discharged at the same speed. The reaction temperature was maintained at 80 ° C, the reaction was continued for 120 hours, and then sampling and analysis were performed every 12 hours; the data in the column of "Long-cycle reaction results" in Table 3 is the average of 5 sampling results after 120 hours of reaction.

[0195] Cyclohexanone conversion rate (%) = (cyclohexanone mole number in the raw material - cyclohexanone mole number in the product) / cyclohexanone mole number in the raw material × 100%;

[0196] Cyclohexanone oxime selectivity (%) = the number of moles of cyclohexanone oxime generated in the product / the number of moles of cyclohexanone consumed to generate all products × 100%;

[0197] Cyclohexanone conversion rate reduction rate (%) = (0.5h cyclohexanone conversion rate - 120h cyclohexanone conversion rate) / 0.5h cyclohexanone conversion rate × 100%;

[0198] Cyclohexanone oxime selectivity reduction rate (%) = (0.5h cyclohexanone oxime selectivity - 120h cyclohexanone oxime selectivity) / 0.5h cyclohexanone oxime selectivity × 100%.

[0199] The reaction product was analyzed by gas chromatography, and the analysis results were quantified by external standard method. The chromatographic analysis conditions were: Agilent-6890 chromatograph, HP-5 capillary column, injection volume 0.5 μL, injection port temperature 280°C. The column temperature was maintained at 100°C for 2 min, then increased to 250°C at a rate of 15°C / min and maintained for 10 min. FID detector, detector temperature 300°C.

[0200] Table 3

[0201]

[0202] Comparing Examples 1 to 12 with Comparative Examples 1 to 4, Examples 1 to 12 adopt the method provided by the present disclosure to prepare titanium silicon molecular sieves that meet the peak areas of the peaks at 210±10nm, 260±10nm and 330±10nm in the UV-Vis spectrum characteristics meet I 260 >I 210 >I 330 , and X1 calculated by formula (1) to (3) is in the range of 1.1 to 2.0, X2 is in the range of 1.6 to 3.3, and X3 is in the range of 2.7 to 3.8. Compared with the molecular sieves prepared in comparative examples 1 to 4, the titanium silicon molecular sieves prepared in embodiments 1 to 12 have higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction, and under long-cycle reaction conditions, the cyclohexanone conversion rate reduction rate and cyclohexanone oxime selectivity reduction rate are lower, and the reaction stability is higher.

[0203] Comparing Examples 1 to 14 with Example 15, it can be seen that the amount of raw material added and the preparation conditions of Example 15 are not within the scope provided by the present disclosure. For example, the amount of raw material added in Example 15 is not within the range of "the molar ratio of silicon source: titanium source: first template: water is 1: (0.01 to 0.10): (0.05 to 0.30): (15 to 30); the weight ratio of molecular sieve intermediate: second template: water is 1: (0.05 to 0.50): (1 to 10)". In the UV-Vis spectral characteristics of the titanium silicalite molecular sieve prepared in Example 15, X2 calculated by formulas (2) to (3) is not in the range of 1.6 to 3.3 and X3 is not in the range of 2.7 to 3.8. Compared with Example 15, the titanium silicalite molecular sieves prepared in Examples 1 to 14 have higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction, and under long-cycle reaction conditions, the cyclohexanone conversion rate reduction rate and cyclohexanone oxime selectivity reduction rate are lower, and the reaction stability is higher;

[0204] Comparing Example 1 with Example 13, it can be seen that the amount of raw material added in Example 1 meets the preferred range of "the molar ratio of silicon source: titanium source: first template: water is 1: (0.03~0.06): (0.10~0.25): (18~25)" and "the weight ratio of molecular sieve intermediate product: second template: water is 1: (0.15~0.45): (2~6)", and Example 13 does not prepare titanium silicon molecular sieve according to the raw material molar ratio and weight ratio within this range; Comparing Example 1 with Example 14, it can be seen that Example 1 synthesizes titanium silicon molecular sieve according to the preferred preparation conditions of the present disclosure, and Example 14 does not synthesize titanium silicon molecular sieve according to the preferred preparation conditions of the present disclosure. Compared with Examples 13 and 14, the titanium silicon molecular sieve prepared in Example 1 has higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction, and under long-cycle reaction conditions, the cyclohexanone conversion rate reduction rate and cyclohexanone oxime selectivity reduction rate are lower, and the reaction stability is higher.

[0205] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0206] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0207] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A titanium silicon molecular sieve, characterized in that: The titanium silicate molecular sieve has the following UV-Vis characteristics: The titanium silicate molecular sieve has peaks at 210±10 nm, 260±10 nm and 330±10 nm in the UV-Vis spectrum, respectively; the peak area of ​​the peak at 210±10 nm in the UV-Vis spectrum of the titanium silicate molecular sieve is recorded as I 210 , the peak area of ​​the spectrum peak at 260±10nm is recorded as I 260 , the peak area of ​​the spectrum peak at 330±10nm is recorded as I 330 , where I 260 >I 210 >I 330 .

2. The titanium silicon molecular sieve according to claim 1, characterized in that: X1 defined by the following formula (1) is any value in the range of 1.1 to 2.0: X1 = I 260 / I 210 Equation (1); Optionally, X2 defined by the following formula (2) is any value in the range of 1.6 to 3.3: X2=I 210 / I 330 Formula (2); Optionally, X3 defined by the following formula (3) is any value in the range of 2.7 to 3.8: X2=I 260 / I 330 Formula (3); Preferably, X1 is any value in the range of 1.3 to 1.6, X2 is any value in the range of 2.0 to 2.8, and X3 is any value in the range of 2.9 to 3.

5.

3. The titanium silicon molecular sieve according to claim 1, characterized in that: The molar ratio of silicon to titanium in the titanium silicon molecular sieve is 1:10-100, preferably 1:16-34; Preferably, the titanium silicate molecular sieve contains at least one cavity structure in the crystal; preferably, the size of a single cavity structure is 15nm to 40nm; further preferably, the total volume of the cavity structure accounts for 20% to 80% of the total volume of the titanium silicate molecular sieve, preferably 50% to 70%.

4. The titanium silicon molecular sieve according to claim 1, characterized in that: The average particle size of the molecular sieve particles of the titanium silicon molecular sieve is 250nm to 400nm, preferably 310nm to 380nm; the BET specific surface area is 440m 2 / g~450m 2 / g, preferably 443m 2 / g~447m 2 / g; micropore volume is 0.16cm 3 / g~0.20cm 3 / g, preferably 0.17cm 3 / g~0.19cm 3 / g; mesopore volume is 0.08cm 3 / g~0.14cm 3 / g, preferably 0.10cm 3 / g~0.12cm 3 / g; Optionally, the relative crystallinity of the titanium silicon molecular sieve is above 80%, preferably above 82%; Preferably, there is a hysteresis loop between the adsorption isotherm and the desorption isotherm of low-temperature nitrogen adsorption of the titanium silicalite; preferably, the initial relative pressure (P / P0) at which the hysteresis loop appears is 0.4-0.

5.

5. A method for preparing titanium silicon molecular sieve, characterized in that: The following steps are involved: S1, mixing a silicon source, a titanium source, a first template and water, and performing a first hydrothermal treatment to obtain a molecular sieve intermediate product; S2, mixing the molecular sieve intermediate product, the second template and water, and performing a second hydrothermal treatment; Wherein, the first template is selected from one or more compounds having the structure shown in the following formula (M-1): wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms; The second template is selected from one or more compounds having the structure shown in the following formula (M-2): Wherein R5, R6, R7 and R8 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms; and there is at least one alkenyl group among R5, R6, R7 and R8.

6. The method according to claim 5, characterized in that In the formula (M-1) of the first template, R1, R2, R3 and R4 are each independently selected from one of an alkyl group having 3 carbon atoms and an alkenyl group having 3 carbon atoms; In the formula (M-2) of the second template, R5, R6, R7 and R8 are each independently selected from one of an alkyl group having 3 carbon atoms and an alkenyl group having 3 carbon atoms; Preferably, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide; The second template is selected from one or more of allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably selected from allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; preferably selected from one or more of allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably selected from one or more of allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide.

7. The method according to claim 5, characterized in that In step S1, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably at least one of organic silicone grease, solid silica gel and white carbon black; Optionally, the organic silicone grease is selected from one or more compounds having a structure represented by the following formula (A): R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate; Optionally, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source; Preferably, the organic titanium source is a titanium-containing organic acid ester, selected from at least one of the structures represented by the following formula (B): Where R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl; Preferably, the inorganic titanium source is selected from one or more of chloride, nitrate or sulfate of titanium; Further preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.

8. The method according to claim 5, characterized in that In step S1, the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water is 1: (0.01-0.10): (0.05-0.30): (15-30), preferably 1: (0.03-0.06): (0.10-0.25): (18-25).

9. The method according to claim 5, characterized in that In step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 150°C to 200°C, the hydrothermal time is 2h to 100h, and the hydrothermal crystallization pressure is the autogenous pressure; preferably, the hydrothermal temperature is 160°C to 190°C, and the hydrothermal crystallization time is 4h to 80h; more preferably, the hydrothermal temperature is 165°C to 188°C, and the hydrothermal crystallization time is 5h to 40h; Optionally, before performing the first hydrothermal treatment, the method further comprises: performing a hydrolysis-dripping alcohol treatment on a raw material mixture obtained by mixing the silicon source, the titanium source, the first template and water; optionally, the conditions of the hydrolysis-dripping alcohol treatment include: treating at 5°C to 120°C for 0.5h to 48h; preferably treating at 50°C to 100°C for 1h to 24h.

10. The method according to claim 5, characterized in that The method further includes: Drying and calcining the solid product obtained by the hydrothermal treatment in step S1 to obtain a first intermediate product; Preferably, the method further comprises: contacting the first intermediate product with a peroxide for mixing treatment to obtain the molecular sieve intermediate product.

11. The method according to claim 10, characterized in that The peroxide is selected from one or more of inorganic peroxides and organic peroxides; optionally, the inorganic peroxide is selected from one or more of hydrogen peroxide, potassium peroxide and sodium peroxide; the organic peroxide is selected from one or more of tert-butyl peroxide, cumene hydroperoxide and meta-chloroperbenzoic acid; Optionally, the peroxide is used in the form of a solution, and the solvent of the peroxide solution is selected from one or more of water, alcohol compounds with 1 to 10 carbon atoms, ester compounds with 2 to 10 carbon atoms, and ketone compounds with 3 to 10 carbon atoms. Preferably, the solvent is selected from one or more of water, n-butanol, tert-butanol, ethanol, methanol, and cyclohexanol. The peroxide concentration in the peroxide solution is 0.1 wt% to 10 wt%, preferably 0.3 wt% to 7 wt%; the pH value is 2.0 to 6.5, preferably 3.0 to 6.0, more preferably 3.7 to 5.0; the weight ratio of the peroxide solution to the first intermediate product is (0.5 to 50):1, preferably (1 to 40):1, more preferably (1.5 to 25):

1.

12. The method according to claim 10, characterized in that The conditions of the calcination treatment include: a calcination temperature of 350°C to 650°C and a calcination time of 2h to 10h; preferably, a calcination temperature of 450°C to 600°C and a calcination time of 4h to 8h; The conditions for mixing the second intermediate product with the peroxide include: a treatment temperature of 25°C to 100°C, preferably 50°C to 95°C, and more preferably 75°C to 85°C; a treatment time of 5min to 1440min, preferably 60min to 1200min, and more preferably 75min to 1000min; and a pressure of 0MPa to 5MPa, preferably 0.2MPa to 2.0MPa.

13. The method according to claim 5, characterized in that In step S2, the weight ratio of the molecular sieve intermediate product: the second template: water is 1: (0.05-0.50): (1-10), preferably 1: (0.15-0.45): (2-6); Optionally, the conditions of the second hydrothermal treatment include: temperature of 150°C to 200°C, time of 2h to 72h, and pressure of autogenous pressure; preferably, temperature of 160°C to 180°C, time of 12h to 48h.

14. Titanium silicon molecular sieve prepared according to the method according to any one of claims 5 to 13.

15. Use of the titanium silicon molecular sieve according to any one of claims 1 to 4 and 14 in catalytic organic reaction and / or adsorption separation process.

16. The use according to claim 15, characterized in that The catalytic organic matter reaction includes propylene epoxidation to prepare propylene oxide, catalytic chlorohydrinization of allyl chloride to prepare dichloropropanol, and cyclohexanone oximation to prepare cyclohexanone oxime; optionally, the cyclohexanone oximation to prepare cyclohexanone oxime includes the following steps: Under oximation reaction conditions, cyclohexanone, an oxidant, ammonia and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve; Optionally, the oxidant is selected from one or more of hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide and m-chloroperbenzoic acid; preferably, the reaction is carried out in the presence of a solvent; the solvent is selected from one or more of n-butanol, tert-butanol, ethanol, methanol and cyclohexanol; Preferably, the oximation reaction conditions include: the molar ratio of the oxidant to cyclohexanone is 1.2 to 2.0:1, the molar ratio of the solvent to cyclohexanone is 0.5 to 5:1, the molar ratio of ammonia to cyclohexanone is 1.0 to 3.0:1, and the weight ratio of the catalyst to cyclohexanone is 0.05 to 0.2:1; the reaction temperature is 60 to 90°C, and the reaction time is 0.3 to 1.0h.

Citation Information

Patent Citations

  • Preparation method and application of thin-layer nanosheet type hierarchical pore TS-1 molecular sieve catalyst

    CN112408414A

  • Titanium-silicon material with core-shell structure, preparation method of titanium-silicon material and method for producing ketoxime through ammoximation reaction of macromolecular ketones

    CN112742470A

  • Titanium silicalite molecular sieve, preparation method thereof and method for producing ketoxime through ammoximation reaction of macromolecular ketones

    CN112744838A

  • TS-1 molecular sieve as well as preparation method and application thereof

    CN113880101A

  • Preparation method and application of cyclohexanone ammoxidation catalyst

    CN115007202A